Loyal soldiers or seasoned leaders? The selection of committee chairs in the European Parliament - Chiru, M (Routledge, 2019)
Although European Parliament committee chairs play a salient role in the legislative process of the EU, we know virtually nothing about their selection and whether policy specialization and the individual attributes of the MEPs matter in the process. This paper draws on a unique longitudinal dataset that includes all full committee members, information on their past committee experience and office in the first seven terms of the EP and data on their parties. Despite the complex proportionality rules that govern the selection of committee chairs in the EP and the interdependence between their distribution and the allocation of other legislative offices, I find that chair seniority shapes the nomination of committee chairs. On the contrary, there is no evidence that European Party Groups use chair selection to reward their most loyal members, while EPG leaders did become chairs more often than regular members in the early terms.